Could Eremotherium laurillardi (Lund, 1842) (Megatheriidae, Xenarthra) be an Omnivore Species? - Dantas, Mário André Trindade; Omena, Érica Cavalcante; Silva, Jorge Luiz Lopes da; Sial, Alcides (Anuário do Instituto de Geociências, 2021)
We present carbon (δ13Ccollagen = -10.1 ‰) and nitrogen (δ15N = 6.8 ‰) isotopic data for E. laurillardi from Brejo da Madre de Deus, Pernambuco (Brazil) and discuss the possibility of an omnivore diet for it. Our data, although ponctual, reinforce the hypothesis that E. laurillardi was a herbivore species.